An examination of Neil Gaiman’s Coraline and The Graveyard book in the context of Gothic Elements and Child Psychology - Prima, Shah Rila Nowal (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.